(untitled) (Superficies y Vacío, 2017)
Copper aluminate (CuAlO2) is a p-type semiconducting thermoelectric material that crystalize in delafosite phase at a temperature of 1100 °C. In this work, two samples were synthesized by Pechini method and calcined using two different procedures in order to determine the effect of thermal history on the phase formation and the thermoelectric properties. Sample M1 was calcined at 1100 °C after a termal treatment at 550 °C and the sample M2 was calcined at 1100 °C without previous treatment. Crystalline structure of obtained materials was analyzed by X-ray diffraction and bandgap energy obtained from Kubelka-Munk method applied to UV-Vis diffuse reflectance spectra. In sample M1 a mixture of spinel and delafossite phases was obtained and in sample M2 a mixture of Al2O3 and delafossite. Electrical conductivity, carrier density and Seebeck effect were measured from 100 °C to 800 °C, confirming that both samples are p-type semiconductors and their conductivity occurs from small polarons. It is shown that temperature ramp and pre-treatment affect the formation of secondary phases, which has a direct effect on thermoelectric properties of the material.